Mark as Story - Thomas, J. (Neotestamentica, 2013)
David Rhoads' and Donald Michie's 1982 Mark as Story: An Introduction to the Narrative of a Gospel was a ground-breaking monograph in NT narrative criticism. At the time, many scholars constrained by the limits of historical criticism began to focus instead on the literary aspects of the NT documents. Rhoads, a biblical scholar, started collaboration with Michie, a professor of literature, on the Gospel of Mark. The result of their joint effort was Mark as Story, which today is still seen as a seminal work for narrative criticism. Almost three decades later, Kelly I. Iverson and Christopher W. Skinner look back to honour the influence of this work while at the same time looking forward to new developments in narrative criticism.